Some Bounds on \(a\)-Analogue Atom-Bond Connectivity Related Indices - Sarveshkumar, B.; Chaluvaraju, B. (Communications in Mathematics and Applications, 2023)
For any non-real number \(a\), the significance of the \(a\)-analogue Atom-Bond Connectivity indices lies within the actuality of their particular cases for well-chosen values for the variant \(a\). In this paper, we obtained some bounds based on the vertex-degree along with the variant \(a\) value, inequalities in other degree-based indices, and characterizations of these novel \(a\)-analogue \(ABC\) indices.